Juridical Analysis of the Use of Cigarette Taxes for Funding the National Health Insurance Program (Case Study of the Supreme Court Decision Number 25 P / Hum / 2018) - Gunawan Nachrawi; Fitriana Dinarwati (Budapest International Research and Critics University, 2021)
Article 2 paragraph (2) Regulation of the Minister of Health Number 53 of 2017 concerning Amendments to the Regulation of the Minister of Health Number 40 of 2016 concerning Guidelines for the Use of Cigarette Taxes for Funding Public Health Services an application for judicial review rights has been submitted to the Supreme Court by OK Petitioners. The formulation of the problems in this thesis are 1) What is the authority of the Supreme Court in examining and deciding judicial cases of Ministerial Regulation 2) What are the considerations of the Panel of Supreme Court Justices in deciding to reject the application for judicial review rights in the Supreme Court Decision Number: 25. The research used is normative legal research with statutory, historical, and conceptual approaches. The results of the research conducted by the Supreme Court are authorized to examine and adjudicate requests for judicial review of the Ministerial Regulation at the Supreme Court. The panel of judges in deciding to reject the Petitioner's petition in case Number: 25 P / HUM / 2018 was actually sufficient based on the Petitioner's legal standing because the Petitioner did not clearly state what rights the object of the petition for judicial review had given to the Petitioner and did not specify the form losses suffered directly by the Petitioner.